2018
DOI: 10.1016/j.cmi.2017.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Colistin exposure as a risk factor for infections caused by inherently colistin resistant Enterobacteriaceae—a case–control study

Abstract: Exposure to colistin is associated with an increased risk of isolating an inherently colistin-resistant Enterobacteriaceae in patients with prolonged hospitalization. This should be taken into account while considering empirical therapy for such patients. Use of colistin should be judicious. The correlation between duration and magnitude of exposure and ICRE infection should be investigated in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Similarly, to nearby countries, colistin resistant K. pneumoniae strains in Israel are genetically diverse with different sequence types including ST16, ST76, ST258, and ST512 (Lalaoui et al, 2019). Indeed, this country lacks quantitative investigation of the dosages and/or duration of colistin administration that significantly increase the risk of development of colistin resistance in a strain or a patient (Drozdinsky et al, 2018).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%
“…Similarly, to nearby countries, colistin resistant K. pneumoniae strains in Israel are genetically diverse with different sequence types including ST16, ST76, ST258, and ST512 (Lalaoui et al, 2019). Indeed, this country lacks quantitative investigation of the dosages and/or duration of colistin administration that significantly increase the risk of development of colistin resistance in a strain or a patient (Drozdinsky et al, 2018).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%
“…A multicenter study collected colistin-resistant Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae from the bloodstreams of patients and found that previous treatment with colistin, a preceding colonization of resistant K. pneumoniae , and a Charlson score of ≥3 were correlated with CoRB infection [60, 61]. Previous treatment with colistin also has been associated with CoR Enterobacteriaceae infection in a matched case control study by Drozdinsky et al [62]. A possible relationship exists between neurological disorders and CoR K. pneumoniae infections [63], though this phenomenon was described only in few researches and needs further verification.…”
Section: Risk Factors and Prognosis For Corb Infectionmentioning
confidence: 99%
“…Colistin is a polymyxin antibiotic that is considered as the final line of treatment for multidrugresistant Gram-negative bacteria (Li et al,2006) and exposure to colistin is associated with an increased risk of isolating colistin-resistant Enterobacteriaceae (Drozdinsky et al, 2017). Also the use of azoles-based antifungals (the most frequently used classes of antifungal therapy) may induce resistance in fungi (Fuentefria et al, 2017).…”
Section: Treatment With Antimicrobialsmentioning
confidence: 99%